Kesejahteraan dalam Perspektif Ekonomi Islam - Agung Eko Purwana (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2014)
The teachings of Islam with its economic ideas have provided the principles of life in establishing relationships with others. It contains directions and at the same time demands that followers do their best and stay away from actions that are considered sinful. Therefore, Islamic economics which is part of the overall teachings of Islam does not just contain a collection of rules but provides a guarantee for the realization of welfare. In this article, the author intends to reveal the clarity of the concept of welfare in the perspective of Islamic economics. Islamic economics views that welfare is not merely a matter of material economic distribution but also involves non-material elements and other fields. Therefore, welfare in the economic field will be upheld along with the establishment of welfare in other fields that function to support and strengthen each other. Islamic economics requires its followers to carry out the overall teachings of Islam in all aspects of their lives. The consequence of this concept is that welfare must be seen as a manifestation of God's command to his servants. So that welfare is a continuous effort of mankind to do their best, both to God and to fellow human beings based on the guidance of Islamic teachings.